"The Future Looks Rad from Where I Stand": A Review of "Claiming Space: Voices of Urban Aboriginal Youth" at the UBC Museum of Anthropology - Dowell, Kristin L. (Anthropologica, 2015)
Curated by Pam Brown and curatorial assistant Elle Mâijâ Tailfeathers, Claiming Space is the first urban Aboriginal youth art exhibit at the MOA.